Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/1941738116633437
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Age-Related Differences on Clinical Tests of Postural Stability

Abstract: Background:The modified Balance Error Scoring System (mBESS) and Y-Balance Test are common clinical measurements of postural control, but little is known about the effect of age on performance of these tasks. The purpose of this study was to examine how healthy child and adolescent athletes perform on 2 common clinical measurements of postural control.Hypothesis:Younger athletes would demonstrate poorer postural control compared with older athletes.Study Design:Cross-sectional study.Level of Evidence:Level 3.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
1
14
1
1
Order By: Relevance
“…We also found no statistically significant difference in reach direction asymmetry between MS and HS football players although HS players displayed roughly 28% greater reach distance difference in the ANT direction and 22% less reach distance difference in the PL direction than MS players. This finding is in contrast to a recent study that reported greater PM and PL reach direction asymmetries in athletes between 10 and 12 years of age in comparison to 16 to 18-yr olds while controlling for sex, BMI, and history of injury [ 46 ]. It is reasonable to suggest that the greater difference in age between groups in the previous study versus that seen in our MS and HS groups was influential in these contrasting results.…”
Section: Discussioncontrasting
confidence: 99%
“…We also found no statistically significant difference in reach direction asymmetry between MS and HS football players although HS players displayed roughly 28% greater reach distance difference in the ANT direction and 22% less reach distance difference in the PL direction than MS players. This finding is in contrast to a recent study that reported greater PM and PL reach direction asymmetries in athletes between 10 and 12 years of age in comparison to 16 to 18-yr olds while controlling for sex, BMI, and history of injury [ 46 ]. It is reasonable to suggest that the greater difference in age between groups in the previous study versus that seen in our MS and HS groups was influential in these contrasting results.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies investigating leg-based postural control in soccer players at different ages (i.e., levels of experience) showed inconsistent findings [3,4,5,6]. Specifically, some studies [3,4] did not detect significant differences between age groups while others [5,6] revealed significant differences in unipedal balance performance in older, more experienced—compared to younger, less experienced—athletes. For example, Butler et al [3] investigated leg differences in maximal reach distances in the Lower Quarter Y Balance Test (YBT-LQ) using soccer players playing at high school, collegiate or professional level.…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed these findings to the more frequent use of the standing leg to stabilize the body during soccer-related movements (e.g., passing and/or kicking). Further, Breen and colleagues [6] argued that motor control strategies might differ between older, more experienced players and younger, less experienced players.…”
Section: Introductionmentioning
confidence: 99%
“…This test has previously been used to identify age-related postural control deficits (22) and the risk of sustaining a lower extremity injury (23). During the assessment, participants stood barefoot with the distal aspect of their right foot on the stance plate and push an indicator box with their left foot as far as possible in the anterior, posteromedial and posterolateral directions, returning to the original standing position without losing balance.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol was repeated with the left foot on the platform and the right foot reaching in each direction. We calculated the asymmetry in each direction of movement, defined as the absolute difference between left and right total reach length in the anterior, posteromedial and posterolateral directions (22).…”
Section: Methodsmentioning
confidence: 99%